Physical and chemical parameters and associated abundance and biovolume of Emiliania huxleyi morphotypes recorded in southern Patagonia during the austral late-spring 2015 and early-spring 2017 - Francisco Díaz-Rosas; Catharina Alves-de-Souza; Emilio Alarcon; Eduardo Menschel; Humberto E González; Rodrigo Torres; Peter von Dassow (PANGAEA, 2021)
Physical and chemical parameters and associated coccolithophores species/Emiliania huxleyi morphotypes abundances and biovolume and co-occurring microplankton abundances recorded in southern Patagonia (~ 50-54 S) during the austral late-spring 2015 (at the end of november) and early-spring 2017 (at the end of september). Given the scarcity of data about coccolithophores in Patagonian waters and the impressive nearly a century spring-summer reports of Emiliania huxleyi blooms around the North Sea and Norwegian fjords system we want to observe what happens in this side of the planet. To do that, we collected seawater containing planktonic organisms at the surface and in some stations up to 75 m depth. Inverted microscopy along with SEM analyses were used to identify and quantify the planktonic items. Determination of salinity and temperature was made with a YSI- 30 Termosalinometer (Yellow Springs, OH, USA) and pCO2 was determined with a Qubit-S157 CO2-analyzer (Kingston, Ontario, Canada). Macronutrients, opal and pH were determined as described in Torres et al. (2020; doi:10.1016/j.ecss.2020.106597). Full carbonate system parameters (including Ωcal) were estimated from pH, AT, salinity, temperature (25 °C as input and in situ temperature as output conditions), pressure (0 dbar as input and depth as output conditions) using CO2Sys Excel macro spreadsheet version 2.1 (Pierrot et al., 2006) with Mehrbach set of solubility constants (Mehrbach et al., 1973) refitted by Dickson and Millero (Dickson and Millero, 1987). To extrapolate full carbonate parameters from pCO2 (onboard sensor) and salinity measurements where alkalinity samples were not directly available, the regression curve for the salinity-AT relationship (μmol kg–1) = 63.4 exttimes salinity + 101 (R2 = 0.99, N = 186; Torres et al., 2020) was used to derive AT estimated from salinity.